ANALISIS PENGARUH NIM, BOPO, LDR, NPL, CAR TERHADAP ROA PADA BANK UMUM NASIONAL DI BURSA EFEK INDONESIA PERIODE 2012-2015 - Lilis Setyowati; Kim Budiwinarto (Universitas Sahid Surakarta, 2017)
In this study the author has the purpose to know the inï¬‚uence of NIM, BOPO, LDR, NPL, and the CAR partially or simultaneously against ROA at national commercial banks in Indonesia Stock Exchange period 2012-2015. Research method using case studies, the data source used for data collectionfrom Bank Indonesia website i.e. www.bi.go.id. The population in this research is national commercial banks in Indonesia Stock Exchange 2012-2015 period, sampling techniques using a purposive sampling, namely an amount of 17 bank companies, methods of data collection used documentation. Technique of data analysis used a classic assumption test, multiple linear regression analysis, t-test, F-test and coeffcient of determination. Based on the research results obtained conclusions as follows: 1) partially known that Net Interest Margin (NIM) positive and signifcant effect against ROA. 2) partially known that operating expenses/operating income (BOPO) a negative and signifcant effect against ROA. 3) partially known that the Loan To Deposit Ratio (LDR) has no effect against ROA. 4) partially known that Non Performing Loan (NPL) a negative and signifcant effect against ROA. 5) partially able to note that the Capital Adequacy Ratio (CAR) have no effect against ROA. 6) simultaneously there is inï¬‚uence signifcant Net Interest Margin (NIM), operatingexpenses/operating income (BOPO), Loan To Deposit Ratio (LDR), Non Performing Loan (NPL), and the Capital Adequacy Ratio (CAR) against ROA.